Effectiveness of Physical Exercise on the Glycemic Control of Type 2 Diabetes Mellitus Patients: A Systematic Review - Yulia Kurniawati; Hurin’in Aisy Baridah; Made Dian Kusumawati; Irfan Wabula (Jurnal Ners, 2019)
Introduction: Type 2 diabetes mellitus (T2DM) is one of the main causes of increasing global health morbidity and mortality for diabetes cases. Increasing the glycemic control in patients with T2DM is not enough if it is only treated with anti-hyperglycemic drugs. Physical exercise is an activity that is planned, structured and carried out to improve health or physical fitness and it is an effective way to improve glycemic control. The aim of this study was to search and review the research on effectiveness of physical exercise on glycemic control in T2DM.Methods: We searched the scientific literature on T2DM and physical exercise in the ScienceDirect, ProQuest, Scopus, Ebsco and Pubmed databases for original research studies and then we reviewed them systematically. Of the 1145 articles retrieved, 14 studies were obtained by the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) methodResults: Aerobic physical exercise improved the glycemic control of T2DM and it was widely used and significant for glycemic control. The schedule of 3 times a week for 60 minutes per session over 2 months was widely used and significant when it came to reducing blood glucose and hemoglobin A1c (HbA1c).Conclusion: This systematic review could be used as evidence when carrying out aerobic physical exercise interventions for the purpose of glycemic control.